1996
DOI: 10.2136/sssaj1996.03615995006000010036x
|View full text |Cite
|
Sign up to set email alerts
|

Furrow Irrigation Water‐Quality Effects on Soil Loss and Infiltration

Abstract: Irrigation-induced erosion is a serious problem in the western USA where irrigation water quality can vary seasonally and geographically. We hypothesized that source-water electrical conductivity (EC) and sodium adsorption ratio (SAR = Na/[(Ca + Mg)/2]° 5, where concentrations are in millimoles of charge per liter) affect infiltration and sediment losses from irrigated furrows, and warrant specific consideration in irrigation-induced erosion models. On a fallow Portneuf silt loam (coarse-silty, mixed, mesic Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…2 dS m -1 ) and low SAR are preferable in irrigation water to prevent soil dispersion, reduce soil erosion, and increase infiltration because of strengthened soil bonds and heightened retention of soil aggregates (Lentz et al, 1996). There was a trace of Na + (0.6 mg L-1 ) in the RO water and no evidence of Ca" and Mg ++ , and therefore a low EC (0.02 dS m-1 ) and an undefined SAR.…”
Section: Soil Test Ro Water Roffap Watermentioning
confidence: 99%
See 1 more Smart Citation
“…2 dS m -1 ) and low SAR are preferable in irrigation water to prevent soil dispersion, reduce soil erosion, and increase infiltration because of strengthened soil bonds and heightened retention of soil aggregates (Lentz et al, 1996). There was a trace of Na + (0.6 mg L-1 ) in the RO water and no evidence of Ca" and Mg ++ , and therefore a low EC (0.02 dS m-1 ) and an undefined SAR.…”
Section: Soil Test Ro Water Roffap Watermentioning
confidence: 99%
“…Water quality available for runoff studies varies depending on source and may differ from rain water quality (Lentz et al, 1996). Therefore, a postulate is that water from various sources may influence runoff and P losses.…”
mentioning
confidence: 99%
“…LENTZ et al (1996) determined that main effects for water quality, traffic, and first vs. second irrigations were significant for total soil loss, mean sediment concentration, total outflow, net infiltration and advance time. Average tail-water soil losses was also most for low EC/high SAR of water treatments and net infiltration decreased 14% in high SAR compared with low SAR treatments too.…”
Section: Water Quality Effect On Soil Erosionmentioning
confidence: 99%
“…Similarly, interactions of soil properties with water are largely limited to physical phenomena via slope, slope length, surface roughness, cover, etc. ; however, laboratory simulations and rain simulator studies (Levy et al, 1994;Shainberg et al, i 994;Kim and Miller, 1996;Flanagan et al, 1997aFlanagan et al, , 1997b as well as furrow irrigation studies (Lentz et al, , 1996 have demonstrated that EC and SAR significantly influence the erosive potential of a given shower or stream of water. Soil chemistry effects, to the extent that they exist in rainfed conditions, are indirectly integrated in rain-induced soil erosion models by affecting soil aggregation and dispersion on wetting.…”
Section: Water Quality Effectsmentioning
confidence: 99%